Acute Effects of Exercise Mode on Arterial Stiffness and Wave Reflection in Healthy Young Adults: A Systematic Review and Meta-Analysis - Pierce, Doris R.; Doma, Kenji; Leicht, Anthony S. (Frontiers in Physiology, 2018)
Background: This systematic review and meta-analysis quantified the effect of acute exercise mode on arterial stiffness and wave reflection measures including carotid-femoral pulse wave velocity (cf-PWV), augmentation index (AIx), and heart rate corrected AIx (AIx75). Methods: Using standardized terms, database searches from inception until 2017 identified 45 studies. Eligible studies included acute aerobic and/or resistance exercise in healthy adults, pre- and post-intervention measurements or change values, and described their study design. Data from included studies were analyzed and reported in accordance with the Cochrane Handbook for Systematic Reviews of Interventions and PRISMA guidelines. Meta-analytical data were reported via forest plots using absolute differences with 95% confidence intervals with the random effects model accounting for between-study heterogeneity. Reporting bias was assessed via funnel plots and, individual studies were evaluated for bias using the Cochrane Collaboration’s tool for assessing risk of bias. A modified PEDro Scale was applied to appraise methodological concerns inherent to included studies. Results: Acute aerobic exercise failed to change cf-PWV (mean difference: 0.00 ms-1 [95% confidence interval: -0.11, 0.11], p = 0.96), significantly reduced AIx (-4.54% [-7.05, -2.04], p = 0.0004) and significantly increased AIx75 (3.58% [0.56, 6.61], p = 0.02).Contrastingly, acute resistance exercise significantly increased cf-PWV (0.42 ms-1 [0.17, 0.66], p = 0.0008), did not change AIx (1.63% [-3.83, 7.09], p = 0.56), and significantly increased AIx75 (15.02% [8.71, 21.33], p < 0.00001). Significant heterogeneity was evident within all comparisons except cf-PWV following resistance exercise, and several methodological concerns including low applicability of exercise protocols and lack of control intervention were identified. Conclusions: Distinct arterial stiffness and wave reflection responses were identified following acute exercise with overall increases in both cf-PWV and AIx75 following resistance exercise potentially arising from cardiovascular and non-cardiovascular factors that likely differ from those following aerobic exercise. Future studies should address identified methodological limitations to enhance interpretation and applicability of arterial stiffness and wave reflection indices to exercise and health.